Analyzing Anxiety’s Speech Acts in Inside Out 2: A Pragmatic Study of Emotional Language and Its Implications for Educational Management - Indri Barauntu; Muh Hasbi; Aslan Abidin (Journal of Educational Management Research, 2026)
This study aims to analyze the types and pragmatic functions of speech acts performed by the character Anxiety in Pixar’s animated film Inside Out 2 and to examine their implications for educational management, particularly in the context of social-emotional learning. Employing a qualitative descriptive approach grounded in Speech Act Theory, the data were obtained from Anxiety’s utterances in the film and analyzed through classification and interpretative techniques. The utterances were categorized based on Searle’s taxonomy of illocutionary acts. The findings reveal that directive and expressive speech acts dominate Anxiety’s language, reflecting its role as a controlling and protective emotion that influences decision-making and emotional regulation during adolescence. Directive acts function to manage behavior and anticipate risk, while expressive acts convey emotional tension, concern, and fear. These results indicate that speech acts in animated films serve as linguistic representations of psychological states. The study implies that understanding emotional speech acts can support educational management practices, particularly in classroom management and social-emotional learning programs, by providing insights into how language shapes emotional regulation, student behavior, and supportive learning environments